2015
DOI: 10.4088/jcp.14m09218
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Male Suicide and Lithium in Drinking Water

Abstract: The present findings suggest that lithium in drinking water may be associated with the low risk of male suicide in the general population. Further studies are required to confirm these findings and investigate gender differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 31 publications
3
56
3
1
Order By: Relevance
“…The lithium levels of water were measured by using mass spectroscopy analyzed by a third party [2,4,5]. This method can measure very small amounts of lithium; the limit of quantification of lithium is 0.1 ppb (0.1 μg/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lithium levels of water were measured by using mass spectroscopy analyzed by a third party [2,4,5]. This method can measure very small amounts of lithium; the limit of quantification of lithium is 0.1 ppb (0.1 μg/L).…”
Section: Methodsmentioning
confidence: 99%
“…Several epidemiological studies have shown the inverse association of lithium levels in tap water and suicide rates [1][2][3][4][5][6], although a few studies failed to find such association [7] or have reported an ambiguous association [8]. However, many people drink both mineral water and tap water.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, an article in this issue of The Journal of Clinical Psychiatry suggests that lithium may decrease suicide rates among men but not among women. 1 This finding may indicate that lithium affects men differently than women.…”
Section: Neurobiologymentioning
confidence: 99%
“…In this issue, Ishii and colleagues 8 present further argument for the hypothesis that even low lithium doses-or rather, doses of lithium at a supplemental level-might have their place in suicide prevention.…”
mentioning
confidence: 99%
“…9,10 However, the estimates of risk reduction by lithium have been criticized as too optimistic, and the first prospective RCTs of lithium versus valproate in bipolar disorder showed no difference in suicide events or attempts between both compounds, 12 which share a common mode of action on glycogen synthase kinase-3β (GSK-3β), brain-derived neurotrophic factor (BDNF), and other neurobiological markers. 13 Besides the general question about lithium's antisuicidal properties, the important point with ecological studies like the one presented by Ishii and colleagues 8 is that natural lithium contents of tap water range up to 1 mg or more of dissolved lithium per liter per day (1 L of water with 1 mg/L lithium per day corresponds to 6.9 mg lithium carbonate per day), depending on the geographic origin of the drinking water. 2,14 Under the assumption that individuals drink not more than 2 L water per day (corresponding to a daily dose of 13.8 mg lithium carbonate by mouth), such an intake would result in a daily dose of approximately 1% of a therapeutic lithium dose.…”
mentioning
confidence: 99%